2022
DOI: 10.1186/s40813-022-00289-4
|View full text |Cite
|
Sign up to set email alerts
|

In the presence of non-neutralising maternally derived antibodies, intradermal and intramuscular vaccination with a modified live vaccine against porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) induce similar levels of neutralising antibodies or interferon-gamma secreting cells

Abstract: The purpose of this study was to compare the immune response generated by the intramuscular and the intradermal vaccination route against the porcine reproductive and respiratory syndrome virus (PRRSV). Piglets from a seronegative and a seropositive farm were selected (n = 28 piglets per farm), and each group was divided into two groups and vaccinated after weaning with modified live vaccine Unistrain® PRRS (Laboratorios Hipra Amer, Spain) by the intramuscular (IM) or the intradermic (ID) route. For the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Additionally, Balasch et al described the capability of an MLV to overcome maternal immunity when this MLV is administered to 1-day-old piglets originating from sows that have been vaccinated once [ 46 ]. Finally, in a recent study by Aguire et al, the use of a heterologous PRRSV vaccine was able to overcome the MDA interference [ 47 ]. Although the use of a heterologous PRRSV vaccine in piglets is beneficial in overcoming the MDA interference, it is not recommended to use different MLV strains in the same herd, given the risk for recombination events [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Balasch et al described the capability of an MLV to overcome maternal immunity when this MLV is administered to 1-day-old piglets originating from sows that have been vaccinated once [ 46 ]. Finally, in a recent study by Aguire et al, the use of a heterologous PRRSV vaccine was able to overcome the MDA interference [ 47 ]. Although the use of a heterologous PRRSV vaccine in piglets is beneficial in overcoming the MDA interference, it is not recommended to use different MLV strains in the same herd, given the risk for recombination events [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, the outbreak of PRRSV has had a significant impact on the economic performance of pig farms, and most of the losses are caused by a decrease in the number of weaned and fattened piglets and an increase in feed costs [ 53 ]. Control of the infection is usually performed by a combination of virus monitoring, biosecurity restrictions, herd management measures and vaccination [ 54 ]. Currently, commercial vaccines provide partial protection only against L1.8 (L1C) PRRSV [ 55 58 ]; therefore, there is an urgent need to develop a commercial vaccine for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…This technology has emerged as the pig industry seeks more effective and safer vaccination methods to enhance animal welfare. Extensive studies have demonstrated that the intradermal (ID) delivery system can provide protection comparable to or better than that provided by the intramuscular (IM) route [ 179 , 199 , 200 , 201 ]. This method is effective for PRRS vaccination, as the skin contains cells from both the innate and adaptive immune systems.…”
Section: Prospective Consideration In Prrsv Control and Vaccine Devel...mentioning
confidence: 99%
“…Following a virus challenge, the IM vaccination group exhibited a higher PRRSV-specific antibody response according to ELISA testing, whereas the ID vaccination group showed the highest expression levels of PRRSV-specific IFN-γ-SC 21 days post vaccination, indicating a stronger cell-mediated immune response [ 179 ]. Additional studies have also shown that ID vaccination of suckling piglets positively affects their health and performance, inducing an immune response equivalent to that achieved with the traditional intramuscular route [ 199 , 200 , 201 ].…”
Section: Prospective Consideration In Prrsv Control and Vaccine Devel...mentioning
confidence: 99%